2011
DOI: 10.1097/opx.0b013e31821ddc6c
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Array Analysis of Tear Proteins in Ocular Cicatricial Pemphigoid

Abstract: Purpose To explore non-invasive, protein-based, membrane array technology as a means to evaluate the global immune and angiogenic profile of tear proteins in patients with active ocular cicatricial pemphigoid (OCP). Methods Forty-three proteins consisting of cytokines, angiogenic/growth factors, and immuno-inflammatory modulators were measured by membrane array in tear samples of four control patients and four OCP patients during active disease and after treatment. Results Signals for several distinct and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Membrane array analysis of OCP tears in active disease revealed markedly elevated MMP-9 thought to be released by activated neutrophils 26 . MPO is a well-established marker of neutrophil infiltration whose activity has been used to quantitate the density of polymorphonuclear cells in corneal and conjunctival tissues 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Membrane array analysis of OCP tears in active disease revealed markedly elevated MMP-9 thought to be released by activated neutrophils 26 . MPO is a well-established marker of neutrophil infiltration whose activity has been used to quantitate the density of polymorphonuclear cells in corneal and conjunctival tissues 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Interblinking microtrauma owing to eyelid margin or cicatrical conjunctival changes are associated with persistent ocular surface inflammation in Stevens-Johnson syndrome and ocular cicatrical pemphigoid. 34,35 Most ocular GVHD patients have concurrent GVHD in other organs and are primarily managed by a general physician. This may delay the diagnosis of ocular GVHD, especially in the early stage, and result in irreversible damage to the ocular surfaces.…”
Section: Tear Osmolarity Has Been Proposed As the ''Goldmentioning
confidence: 99%
“…As for flare in the anterior chamber, we measured aqueous protein levels directly, because it was often difficult to assess the flare accurately using slit-lamp microscopy in the eyes with corneal opacity. We excluded 18 eyes with ocular comorbidities (8 eyes with a history of exfoliation syndrome, 3 eyes with chemical burn, 2 eyes with ocular cicatricial pemphigoid, 1 eye with aniridia, 1 eye with endotheliitis, 1 eye with Stevens-Johnson syndrome, 1 with exposure keratitis, and 1 eye with iritis), because previous studies showed that aqueous cytokine levels are elevated in eyes with exfoliation syndrome due to breakdown of the blood-aqueous barrier (BAB), 19 and that tear cytokine levels are elevated in inflammatory ocular surface diseases, 20,21 which can affect aqueous cytokine levels due to breakdown of the corneal epithelial barrier. 22 In the eyes with cataract and bullous keratopathy, when we perform two-step surgery, we always perform cataract surgery first, followed by DSAEK, with an interval of more than 3 months.…”
Section: Patientsmentioning
confidence: 99%